Leptin Gene Polymorphism (–2548 G/A) and Its Relationship With Serum Leptin in Polycystic Ovary Syndrome - Suat Cakina; Emine Sevinc Postacı; Ibrahim Eren Pek; Basak Nil Sen; Fatma Beyazit (Discovery Medicine, 2026)
Background: Polycystic ovary syndrome (PCOS) is a common hormone disorder in women of reproductive age. It is often associated with changes in adipokine signaling, obesity, and insulin resistance. The leptin gene produces a hormone that helps control energy balance and reproductive health. The –2548G>A promoter polymorphism in this gene might affect how leptin is expressed and metabolized, but findings have differed between populations. This study aims to investigate the distribution of –2548G>A genotypes and serum leptin levels in women with PCOS.Methods: The study included 100 women with PCOS and 100 healthy controls of similar age, recruited between July 2023 and September 2025. Researchers measured physical, hormonal, and metabolic factors. They used enzyme-linked immunosorbent assay (ELISA) to check serum leptin levels and polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) to identify –2548G>A genotypes. Data analysis was done with SPSS version 25.0.Results: There were no significant differences between the groups in age, body mass index, or other biochemical and hormonal measures (p > 0.05). However, the A/A genotype of the –2548G>A polymorphism was more common in the PCOS group than in controls (p = 0.03). There was no significant link between –2548G>A genotypes and blood leptin levels.Conclusions: The –2548G>A polymorphism may raise the risk of developing PCOS, but it does not seem to affect blood leptin levels. Larger studies that include leptin receptor variants and functional tests are needed to better understand how leptin regulated in PCOS.